2020
DOI: 10.1007/s11164-020-04236-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and application of Fe-pillared bentonite to the removal of Coomassie blue dye from aqueous solutions

Abstract: This study aims to prepare the sodium bentonite (Bent-Na) and the iron-pillared bentonite (PILC-Fe) and to evaluate its adsorption efficacy against Coomassie blue from aqueous solution. Results demonstrated that the PILC-Fe sample presents an increase in the basal distance d 001 from 13.66 to 16.93 Å. The presence of the Fe-O and FeOOH functional group band on PILC-Fe was confirmed by FTIR analysis. A clear increase has been observed of the specific surface area from 45.86 to 125.30 m 2 /g for Bent-Raw and PIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…The diffraction peaks at 6°, 17°, 20°, 35°, 73.8° corresponds to the montmorillonite [28], [29]. The peaks at 21 ° and 27 ° are related to the presence of silica [28]. The presence of kaolinite is con-firmed by the presence of diffraction peaks at 12°, 34°, 59° and 94° [29].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The diffraction peaks at 6°, 17°, 20°, 35°, 73.8° corresponds to the montmorillonite [28], [29]. The peaks at 21 ° and 27 ° are related to the presence of silica [28]. The presence of kaolinite is con-firmed by the presence of diffraction peaks at 12°, 34°, 59° and 94° [29].…”
Section: Resultsmentioning
confidence: 96%
“…The figure 3 shows the XRD analysis of the bentonite used in this study. The diffraction peaks at 6°, 17°, 20°, 35°, 73.8° corresponds to the montmorillonite [28], [29]. The peaks at 21 ° and 27 ° are related to the presence of silica [28].…”
Section: Resultsmentioning
confidence: 97%
“…Batch adsorption equilibrium experiments indicated that the adsorbed amount of BM dye by sodium clay was about 330 mg/g with a rapid initial step and reach equilibrium within 20 min [44] . Also, Dhananasekaran et al studied the adsorption MB dye by α-Chitin Nanoparticles [5]. The adsorption process achieved maximum at adsorbed amount about 6.9 mg/g within 30 min.…”
Section: Mb Dye Adsorptionmentioning
confidence: 99%
“…pH of the aqueous solution, is an important parameter that affects the dye adsorption behavior [5]. Indeed, the adsorption behavior of MB dye on nanocomposite has been studied over a wide range of pH 1-10.2 by adding HCl or NaOH to adjust the desired pH value.…”
Section: Effect Of Solution Ph On Mb Uptakementioning
confidence: 99%
See 1 more Smart Citation